New Zealand secondary technology teachers’ perceptions: “technological” or “technical” thinking? - Reinsfield, E.; Williams, John (Kluwer Academic Publishers, 2017)
Technology education in the New Zealand context has seen significant change since it’s inception as a technical subject. The changing nature of the subject in New Zealand secondary schools is influenced by some teachers’ preoccupation with the making of quality product outcomes, rather than their enactment of the curriculum, which conceptualises a wider remit. Research into the perceptions of technology teachers’ interpretation and enactment of the curriculum suggests that to enable change, teachers need to adopt a form of “technological thinking”, in support of their “technical thinking”. Technological thinking is a notion presented to support teachers to explore a range of differing pedagogical approaches and learning outcomes, reflective of the intent of the New Zealand curriculum, which aims to foster learning environments that are innovative and responsive to students’ social and academic needs.